Congenital Contractural Arachnodactyly - J Gordon Millichap (Pediatric Neurology Briefs)
An infant girl with arachnodactyly and spontaneously resolving contractures who died in cardiac failure is reported from the Paediatric Unit, Northern General Hospital and Department of Ophthalmology, Royal Hallamshire Hospital, Sheffield, England.